The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.
Chat with our AI personalities
4x + 3y=9 x=0 y=3
6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
To simplify the expression 2x + 3y + 4x + 9y, you first combine like terms. Adding the coefficients of x terms gives 2x + 4x = 6x. Similarly, adding the coefficients of y terms gives 3y + 9y = 12y. Therefore, the simplified expression is 6x + 12y.
4x-2y
It's the equation of a straight line. Every point on the line is a solution to the equation. There are an infinite number of them.